PERILAKU OPORTUNISTIK MEKANISME PENGAWASAN DAN FINANCIAL DISTRESS TERHADAP MANAJEMEN LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Wandi, Sessy Wira (Balance : Jurnal Akuntansi dan Bisnis, 2022)
This study aims to analyze the effect of opportunistic behavior, leverage and financial distress on earnings management with managerial ownership as a moderator. This research was conducted by quantitative methods using secondary data. The Secondary data consists of data on the date of issuance of the company's financial statements on the IDX website and companies’ annual reports that have been listed on the IDX in 2017-2019. The research population is infrastructure, utility and transportation sector companies listed on the IDX. The sample selection procedure used purposive sampling method with a total sample size of 33 companies and the analysis technique used was moderated regression analysis (MRA). The results of the study prove that opportunistic behavior, monitoring mechanism, and financial distress have an effect on earnings management, managerial ownership as a moderating variable strengthens the relationship between opportunistic behavior and monitoring mechanism with earnings management and weakens the relationship between financial distress and earnings management